Cubic tin selenide-based thermoelectric crystal and preparation method thereof
Through cooling crystallization method and high-temperature sway smelting technology, cubic tin selenide-based single crystals were prepared, solving the problems of difficulty in preparing cubic tin selenide single crystals in the prior art and unstable performance, and realizing the preparation of high-performance thermoelectric materials.
Patent Information
- Application Number
- CN202411726252.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to effectively prepare cubic tin selenide single crystals, which leads to a phase change in the high-temperature structure that affects the measurement and regulation of thermoelectric properties. The layered single crystal structure is easy to dissociate, has strong anisotropy in performance, and has high preparation cost.
Cubic tin selenide-based thermoelectric crystals are prepared by high-temperature sway smelting and multi-stage slow cooling methods, achieving extremely high grain orientation and uniform distribution of four elements.
The prepared cubic tin selenide-based single crystal material does not have a crystal structure phase change, and its performance is reliable, the conductivity and thermal conductivity are significantly improved. The comprehensive thermoelectric superiority reaches 0.7, and it has better thermoelectric properties.
Smart Images

Figure CN119530948A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of crystal synthesis, and in particular to a cubic tin selenide-based thermoelectric crystal and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Thermoelectric technology (TE) has great application prospects in the recovery of low-quality waste heat because it can realize the direct conversion between heat and electricity. Based on the two major physical effects of Seebeck effect and Peltier effect, thermoelectric materials can be used for applications such as temperature difference power generation, thermoelectric refrigeration, and precise temperature control. Thermoelectric devices are solid-state structures with simple structures, no moving parts, and no pollutant emissions.
[0004] Tin selenide (SnSe) with an orthorhombic structure is a simple, green and environmentally friendly sulfide thermoelectric material system. Its distorted rock salt structure causes the Sn-Se bond to have strong anharmonicity, which gives it excellent thermoelectric properties. However, the high-temperature structural phase transition of the material itself directly affects the measurement, regulation and service of the material's high-temperature thermoelectric properties. Theoretical and experimental confirmations show that tin selenide alloys have a highly symmetric cubic structure. Interestingly, cubic phase tin selenide also has strong anharmonicity. In addition, thanks to the high crystal structure symmetry and the relativistic effect of spin-orbit coupling, cubic tin selenide has obtained a higher band degeneracy, giving cubic tin selenide potentially excellent thermoelectric properties.
[0005] The preparation of cubic tin selenide is mainly based on two strategies. The first strategy is to obtain cubic tin selenide thin films on NaCl, Bi2Se3 and other substrates by molecular beam epitaxy technology. The second strategy is to synthesize cubic tin selenide single crystals using the alloy solid solution strategy. Limited by the lack of research on the intrinsic properties of cubic tin selenide, the research progress of its thermoelectric transport properties is slow. Crystal materials are an effective carrier for studying the intrinsic properties of materials, so it is necessary to develop a method for preparing cubic phase tin selenide single crystals.
[0006] The technical document "Mao Lisha. Preparation of tin selenide crystals and their electrothermal transport properties [D]. University of Chinese Academy of Sciences (Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences), 2020." discloses a method for preparing layered SnSe single crystals, but does not involve the preparation of cubic phase tin selenide single crystals. The layered single crystal structure is easy to dissociate, the performance exhibits strong anisotropy, and the cost of sample preparation and cutting is high. There is also a high-temperature phase transition, which is not conducive to the precise measurement and regulation of high-temperature performance, and is not conducive to recycling. The Chinese patent "A tin selenide-based thermoelectric material, its preparation method and application" with application publication number "CN111710775A" discloses a method for preparing cubic phase tin selenide polycrystals, but it is significantly different from single crystal preparation. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a cubic tin selenide-based thermoelectric crystal and a preparation method thereof, and to prepare a cubic tin selenide-based single crystal based on a cooling crystallization method.
[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0009] In a first aspect, a method for preparing a cubic tin selenide-based thermoelectric crystal comprises the following steps:
[0010] S1. Weigh tin (Sn), silver (Ag), antimony (Sb) and selenium (Se) according to the stoichiometric ratio and place them in a first container, evacuate and seal the first container;
[0011] S2, raising the temperature of the first container to 953-1373K and keeping it warm for 15-30 hours, and then lowering the temperature to 773-923K and keeping it warm for 15-30 hours;
[0012] S3, taking out the alloy ingot in the first container, crushing it and placing it in a second container, evacuating and sealing the second container;
[0013] S4, raising the temperature of the second container to 973-1373 K and keeping it at that temperature for 5-30 hours, then cooling it to 923-1173 K at a set first cooling rate, then cooling it to 873-923 K at a set second cooling rate, and then cooling it to room temperature at a set third cooling rate.
[0014] Optionally, in S1, the first container includes an outer first sealed tube and an inner first sealed tube placed therein, and the tin, silver, antimony and selenium elements are placed in the inner first sealed tube.
[0015] Optionally, in S1, the air pressure in the inner first sealed tube is lower than 1.0 Pa; and the air pressure in the gap between the outer first sealed tube and the inner first sealed tube is lower than 1.0 Pa.
[0016] Optionally, in S2, the heating rate is 0.5 to 10 K / min, and the cooling rate is 1 to 10 K / min.
[0017] Optionally, in S2, swing melting is performed during the insulation process between heating and cooling, and the swing rate is 10 to 200 times / min.
[0018] Optionally, in S2, cold water quenching or natural cooling is performed after the cooling and heat preservation process is completed.
[0019] Optionally, in S3, the crushing method is to crush the alloy ingot into particles with a particle size of 0.5 to 8 mm.
[0020] Optionally, in S3, the second container includes an outer second sealed tube and an inner second sealed tube placed therein, and particles of the alloy ingot are placed in the inner second sealed tube.
[0021] Optionally, in S3, the air pressure in the inner second sealed tube is lower than 1.0 Pa; and the air pressure in the gap between the outer second sealed tube and the inner second sealed tube is lower than 1.0 Pa.
[0022] Optionally, in S4, the heating rate is 0.5 to 5 K / min, the first cooling rate is 0.01 to 0.05 K / min, the second cooling rate is 0.01 to 0.05 K / min, and the third cooling rate is 0.1 to 1.0 K / min.
[0023] In a second aspect, the cubic tin selenide-based thermoelectric crystal prepared by the above-mentioned preparation method of the cubic tin selenide-based thermoelectric crystal is a cubic tin selenide-based single crystal, and the chemical formula is Sn 1-2X (AgSb) X Se, 0.1≤X≤0.3.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1. The present invention prepares a bulk cubic tin selenide single crystal material by high-temperature swing melting method and cooling crystallization method, achieving extremely high grain orientation, and the four elements of tin, silver, antimony and selenium are evenly distributed, which is helpful for studying the intrinsic properties of the material. Compared with the layered cubic tin selenide single crystal material, the cubic phase single crystal prepared by the present invention does not have a crystal structure phase change, and it is easy to achieve accurate material and regulation of sample performance; and the cubic structure is more mechanically stable than the layered structure, and will not dissociate; compared with the cubic phase polycrystal, the cubic phase single crystal prepared by the present invention has better electrical transport performance, thereby obtaining better comprehensive thermoelectric performance. In addition, the preparation of single crystal materials is more conducive to the study of the charge transport mechanism of the material, eliminating the influence of grain boundaries on the electrical and thermal properties of the material.
[0026] 2. The carrier concentration of the sample prepared by the present invention is 8.8×10 19 cm -3 ; The electrical conductivity is effectively improved: up to 200S cm at room temperature and high temperature -1 With 280S cm -1 ; The thermal conductivity at room temperature and high temperature is 0.75Wm -1 K -1 With 0.85Wm -1 K -1 The comprehensive thermoelectric figure of merit can reach 0.7 at 823K, making it a high-performance thermoelectric material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1 This is a schematic diagram of the second container in Example 1.
[0029] Figure 2 This is the X-ray diffraction detection spectrum of the sample block in Example 1.
[0030] Figure 3 This is the X-ray diffraction detection spectrum of the sample powder in Example 1.
[0031] Figure 4 This is a scanning electron microscope morphology image of the sample block in Example 1.
[0032] Figure 5 These are the electron backscatter diffraction element distribution diagrams of the sample block in Example 1, (a) is the Sn element distribution diagram, (b) is the Ag element distribution diagram, (c) is the Sb element distribution diagram, and (d) is the Se element distribution diagram.
[0033] Figure 6 This is a curve diagram showing the change of conductivity of the sample block in Example 1 with temperature.
[0034] Figure 7 This is a curve chart showing the Seebeck coefficient of the sample block in Example 1 as a function of temperature.
[0035] Figure 8 This is a curve diagram showing the change of thermal conductivity of the sample block in Example 1 with temperature.
[0036] Fig. 9 This is a curve chart showing the change of the thermoelectric figure of merit of the sample block in Example 1 with temperature.
[0037] Among them, 1. a pointed bottom cylindrical sample; 2. an inner second sealing tube; 3. an outer second sealing tube; 4. a quartz glass plug. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0039] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0040] A method for preparing a cubic tin selenide-based thermoelectric crystal, comprising the steps of:
[0041] S1. Weigh tin, silver, antimony and selenium according to the stoichiometric ratio and place them in a first container, evacuate and seal the first container;
[0042] S2, raising the temperature of the first container and its contents to 953-1373K and keeping it at that temperature for 15-30h, then cooling it to 773-923K and keeping it at that temperature for 15-30h, and then cooling it to room temperature;
[0043] S3, taking out the alloy ingot in the first container, crushing it and placing it in a second container, evacuating and sealing the second container;
[0044] S4. Raise the temperature of the second container and its contents to 973-1373 K, and keep it at this temperature for 5-30 hours, then cool it to 923-1173 K at a first cooling rate, then cool it to 873-923 K at a second cooling rate, and then cool it to room temperature at a third cooling rate.
[0045] In the above process, cubic tin selenide-based single crystals are synthesized by using the strategy of alloy solid solution, and silver and antimony are used to promote the formation of cubic tin selenide. In S4, a multi-stage slow cooling method is used to prepare cubic tin selenide-based single crystals.
[0046] Optionally, in S1, the first container includes an outer first sealed tube and an inner first sealed tube placed therein, and the tin, silver, antimony and selenium elements are placed in the inner first sealed tube; the inner first sealed tube is a quartz glass tube, and the outer first sealed tube is a larger quartz glass tube.
[0047] Optionally, in S1, the air pressure in the inner first sealed tube is lower than 1.0Pa; the air pressure in the gap between the outer first sealed tube and the inner first sealed tube is lower than 1.0Pa; during preparation, after the inner first sealed tube is evacuated, the quartz glass tube is heated by flame, and the heating position is rotated along the axial direction until the quartz glass tube is sealed, and then the inner first sealed tube is placed in the outer first sealed tube, and a quartz glass plug for sealing is placed, the above-mentioned vacuum operation is repeated, and sealing is performed in the same way, and the flame heating position is located at the quartz glass plug.
[0048] Optionally, in S2, the heating rate is 0.5 to 10 K / min, and the cooling rate is 1 to 10 K / min, so that the components can be fully and evenly diffused and the container can be prevented from bursting.
[0049] Optionally, in S2, swing melting is performed during the insulation process between heating and cooling. Under the same temperature and time conditions, swinging can make the sample mixed and react more fully. The swinging rate is 10 to 200 times / min. The equipment used for swing melting is a high-temperature swinging furnace, which is a common equipment for promoting uniform dispersion of various components.
[0050] Optionally, in S2, cold water quenching or natural cooling is performed after the cooling and heat preservation process is completed. Water cooling quenching can shorten the preparation cycle.
[0051] Optionally, in S3, the crushing method is to crush the alloy ingot into particles with a particle size of 0.5 to 8 mm. The particle size needs to be compatible with the tube diameter of the inner second sealing tube, which is helpful for subsequent preparation of crystal materials.
[0052] Optionally, in S3, the second container includes an outer second sealed tube and an inner second sealed tube placed therein, the particles of the alloy ingot are placed in the inner second sealed tube, the inner second sealed tube is a quartz glass tube with a pointed bottom, and the outer second sealed tube is a quartz glass tube of larger size.
[0053] Optionally, in S3, the air pressure in the inner second sealed tube is lower than 10.0 Pa; the air pressure in the gap between the outer second sealed tube and the inner second sealed tube is lower than 10.0 Pa, and the preparation method is the same as the vacuuming and sealing method in S1.
[0054] Optionally, in S4, the heating rate is 0.5 to 5 K / min; the first cooling rate is 0.01 to 0.05 K / min, the second cooling rate is 0.01 to 0.05 K / min, and the third cooling rate is 0.1 to 1.0 K / min, so as to obtain high-quality crystals.
[0055] Optionally, in S4, the second container is maintained in a vertical position, and the equipment is a high-temperature annealing furnace, or a suspended zone melting furnace, so that the internal components are crystallized in a stable equilibrium state to obtain a cubic tin selenide-based thermoelectric crystal product.
[0056] The cubic tin selenide-based thermoelectric crystal prepared by the preparation method of the cubic tin selenide-based thermoelectric crystal is a cubic tin selenide-based single crystal with a chemical formula of Sn 1-2X (AgSb) X Se, 0.1≤X≤0.3.
[0057] Example 1
[0058] A cubic tin selenide-based thermoelectric crystal with the chemical formula Sn 0.5 (AgSb) 0.25 Se, the preparation method comprises the following steps.
[0059] S1. According to the stoichiometric ratio, 15.16310000g of tin, 6.88910000g of silver, 7.77635000g of antimony and 20.17145000g of selenium with a purity of 99.999% were weighed respectively and placed in a quartz glass tube (i.e., the first inner sealed tube) with a diameter of 12.7 mm. The vacuum pump connected to the first inner sealed tube was turned on to evacuate for 10 minutes and ensure that the air pressure in the tube was lower than 10.0 Pa. Then, the molecular pump connected to the first inner sealed tube was turned on to further evacuate for 10 minutes until the air pressure in the tube was lower than 1.0 Pa; then use acetylene flame to heat, and rotate the heating position along the axial direction of the inner first sealed tube until the inner first sealed tube is sealed; put the inner first sealed tube into a quartz glass tube with a diameter of 20 mm (i.e., the outer first sealed tube), and put in a quartz glass plug, repeat the above vacuum operation until the air pressure in the tube is lower than 1.0 Pa, use acetylene flame to heat the position of the quartz glass plug, and rotate the heating position along the axial direction of the outer first sealed tube until the outer first sealed tube is sealed, so as to obtain a first container sealed with the preparation raw materials.
[0060] S2. Place the first container obtained in S1 vertically in a high-temperature swing furnace for melting operation. The process conditions of the melting operation are set as follows: first, slowly heat up to 1273K at a rate of 5K / min, then turn on the swing switch, and keep it in this temperature zone for 20 hours, and swing it at a rate of 50 times / min; after the insulation and swinging are completed, turn off the swing switch; then cool down to 873K at a rate of 5K / min, and keep it at this temperature for 20 hours, and cool it naturally after the insulation process is completed.
[0061] S3. Take out the molten alloy ingot from the completely cooled first container, crush and grind it in a mortar to obtain uniform particles with a particle size of less than 5 mm, take 45 g of the particles and put them into a pointed bottom quartz glass tube with a diameter of 15 mm (i.e., the inner second sealed tube), and use a vacuum pump and a molecular pump to evacuate the tube until the air pressure in the tube is lower than 1.0 Pa in accordance with the method of S1, and then use an acetylene flame to seal the inner second sealed tube, and then put the inner second sealed tube into a quartz glass tube with a diameter of 20 mm (i.e., the outer second sealed tube), and repeat the above vacuum operation until the air pressure in the tube is lower than 1.0 Pa, and then use an acetylene flame to heat the quartz glass plug position, and rotate the heating position along the axial direction of the outer second sealed tube until the outer second sealed tube is sealed to obtain a second container sealed with alloy ingot particles.
[0062] S4. Place the second container vertically in a high-temperature annealing furnace, first heat it to 1223K at a rate of 2K / min and keep it at that temperature for 10h, then cool it to 1073K at a rate of 0.015K / min, then cool it to 973K at a rate of 0.02K / min, and then cool it to room temperature at a rate of 0.5K / min. Figure 1 As shown, the pointed bottom cylindrical sample 1 is still sealed inside the inner second sealed tube 2, and the inner second sealed tube 2 is still sealed inside the outer second sealed tube 3; the quartz glass plug 4 blocks the tube mouth of the outer second sealed tube 3 and remains fused with the outer second sealed tube 3 to maintain the seal; the second container is opened to obtain a pointed bottom cylindrical sample with a diameter of 15 mm.
[0063] Example 2
[0064] A cubic tin selenide-based thermoelectric crystal with the chemical formula Sn 0.4 (AgSb) 0.3 Se, the preparation method is different from that of Example 1 in that:
[0065] In S1, 12.15465000 g of tin with a purity of 99.999%, 8.9.35020000 g of silver, 9.35020000 g of antimony, and 20.21170000 g of selenium with a purity of 99.999% were weighed respectively according to the stoichiometric ratio.
[0066] In S2, the temperature was raised to 1373 K at a rate of 10 K / min and kept at this temperature for 15 h, then cooled to 923 K at a rate of 10 K / min and kept at this temperature for 15 h, and then cooled to room temperature by water cooling.
[0067] In S4, the temperature was first raised to 1373 K at a rate of 5 K / min and kept at this temperature for 5 h, then cooled to 1173 K at a rate of 0.05 K / min, then cooled to 923 K at a rate of 0.03 K / min, and then cooled to room temperature at a rate of 1.0 K / min. The second container was opened to obtain a pointed-bottom cylindrical sample with a diameter of 15 mm.
[0068] Example 3
[0069] A cubic tin selenide-based thermoelectric crystal with the chemical formula Sn 0.4 (AgSb) 0.3 Se, the preparation method is different from that of Example 1 in that:
[0070] In S1, 12.15465000 g of tin with a purity of 99.999%, 8.9.35020000 g of silver, 9.35020000 g of antimony, and 20.21170000 g of selenium with a purity of 99.999% were weighed respectively according to the stoichiometric ratio.
[0071] In S2, the temperature was raised to 953 K at a rate of 0.5 K / min and kept at this temperature for 30 h, then cooled to 773 K at a rate of 1 K / min and kept at this temperature for 15 h, and then cooled to room temperature by water cooling.
[0072] In S4, the temperature was first raised to 973 K at a rate of 0.5 K / min and kept at this temperature for 30 h, then cooled to 923 K at a rate of 0.03 K / min, then cooled to 873 K at a rate of 0.01 K / min, and then cooled to room temperature at a rate of 0.1 K / min. The second container was opened to obtain a pointed-bottom cylindrical sample with a diameter of 15 mm.
[0073] Comparative Example 1
[0074] A cubic tin selenide-based thermoelectric crystal, the chemical formula of which is Sn0.5(AgSb)0.25Se, the preparation method of which is different from that of Example 1 in that:
[0075] In S1, the double-tube method is not used. After the sample is swayed and melted, the quartz glass tube may break during the cooling process, which may cause the sample to come into contact with air and oxidize, resulting in failure of subsequent experiments or damage to material properties.
[0076] Comparative Example 2
[0077] A cubic tin selenide-based thermoelectric crystal, the chemical formula of which is Sn0.5(AgSb)0.25Se, the preparation method of which is different from that of Example 1 in that:
[0078] In S2, after the heat preservation and swinging are completed, the swing switch is turned off; then the temperature is lowered to 873K at a rate of 5K / min, and then directly cooled naturally. In this case, the sample elements are unevenly distributed, which ultimately leads to the inability to synthesize single crystal samples.
[0079] Comparative Example 3
[0080] A cubic tin selenide-based thermoelectric crystal, the chemical formula of which is Sn0.5(AgSb)0.25Se, the preparation method of which is different from that of Example 1 in that:
[0081] In S4, the second container was placed vertically in a high-temperature annealing furnace, and was first heated to 1223 K at a rate of 2 K / min and kept at that temperature for 10 h. Then, a two-stage cooling method was adopted, in which the temperature was cooled to 973 K at a rate of 0.02 K / min, and then cooled to room temperature at a rate of 0.5 K / min. Too fast a cooling rate caused the sample to break.
[0082] Comparative Example 4
[0083] A cubic tin selenide-based thermoelectric crystal with the chemical formula Sn 0.5 (AgSb) 0.25 Se, the preparation method is different from that of Example 1 in that:
[0084] In S4, after the insulation was completed, the temperature was cooled to 1073 K at a rate of 0.1 K / min, then to 973 K at a rate of 0.2 K / min, and then to room temperature at a rate of 1.5 K / min. Too fast a cooling rate also caused the sample to break.
[0085] Test content
[0086] The performance of thermoelectric materials is characterized by a dimensionless parameter (thermoelectric figure of merit, zT): zT = σS 2 T / κ.
[0087] In the right side of the formula, σ, S, T and κ are conductivity, Seebeck coefficient, absolute temperature and thermal conductivity respectively, and σS is defined as 2 is the power factor (PF);
[0088] κ=κ e +κ l +κ b , that is, the total thermal conductivity is the electronic thermal conductivity (κ e ), lattice thermal conductivity (κ l ) and bipolar thermal conductivity (κ b ) and.
[0089] From the zT expression, it can be seen that high-performance thermoelectric materials need to have excellent electrical conductivity, Seebeck coefficient and low thermal conductivity.
[0090] The sample block obtained in Example 1 was subjected to X-ray diffraction detection, and the spectrum is as follows: Figure 2 As shown; the sample block obtained in Example 1 was ground into powder and then subjected to X-ray diffraction detection, the spectrum is as shown Figure 3 As shown, it conforms to the characteristics of cubic tin selenide-based thermoelectric crystals; it can be seen that the block prepared in Example 1 has an extremely high grain orientation degree and only one diffraction peak, indicating that the entire block has only one crystal phase, reflecting that the sample prepared in Example 1 is a single-oriented bulk single crystal material, which is different from the layered single crystal and cubic tin selenide polycrystal in the background technology.
[0091] The scanning electron microscope morphology of the sample block obtained in Example 1 is as follows: Figure 4 As shown, the electron backscatter diffraction element distribution diagram under the same field of view is as follows Figure 5 As shown, Figure 5 (a) is the Sn element distribution diagram. Figure 5 (b) is the Ag element distribution diagram. Figure 5 (c) is the Sb element distribution diagram. Figure 5 (d) is the Se element distribution diagram, from which it can be seen that the four elements are evenly distributed.
[0092] The curve of the conductivity of the sample block obtained in the detection example 1 as a function of temperature is as follows: Figure 6 As shown in Figure 2, near room temperature, the conductivity gradually decreases with increasing temperature; then, the conductivity of the sample increases with increasing temperature, showing semiconductor transport behavior; the maximum value of ~290S cm-1 is obtained at 823K. -1 The curve of Seebeck coefficient changing with temperature is as follows: Figure 7 As shown in Figure 1, unlike the trend of electrical conductivity changing with temperature, the Seebeck coefficient gradually increases with increasing temperature. The curve of thermal conductivity changing with temperature is shown in Figure 1. Figure 8 As shown in Figure 2, with the increase of temperature, the thermal conductivity of the sample first decreases and then increases. At around 600K, the lowest thermal conductivity value is 0.69 W m -1 K -1 The curve of the thermoelectric figure of merit of the sample block of Example 1 obtained above as a function of temperature is as follows: Fig. 9 As shown, the sample finally achieved the maximum thermoelectric figure of merit of ~0.7 at 823K.
[0093] The carrier concentration of the sample block in Example 1 was detected at room temperature and was 8.8×10 19 cm -3 .
[0094] Correspondingly, when the samples of comparative example 1 are tested, their performance is poor or a complete single crystal material cannot be obtained.
[0095] Compared with the layered SnSe single crystal in the background art, the performance advantage of the present application is reflected in: having more beneficial electrical transport performance.
[0096] Compared with the cubic phase tin selenide polycrystal in the background art, the advantage of the present application is that the electrical conductivity near room temperature is higher.
[0097] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a cubic tin selenide-based thermoelectric crystal, characterized in that the steps include: S1. Weigh tin, silver, antimony and selenium according to the stoichiometric ratio and place them in a first container, evacuate and seal the first container; S2, raising the temperature of the first container to 953-1373K and keeping it warm for 15-30 hours, and then lowering the temperature to 773-923K and keeping it warm for 15-30 hours; S3, taking out the alloy ingot in the first container, crushing it and placing it in a second container, evacuating and sealing the second container; S4, raising the temperature of the second container to 973-1373 K and keeping it at that temperature for 5-30 hours, cooling it to 923-1173 K at a first cooling rate, then cooling it to 873-923 K at a second cooling rate, and then cooling it to room temperature at a third cooling rate.
2. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: The first container comprises an outer first sealed tube and an inner first sealed tube placed therein, and the tin, silver, antimony and selenium single substances are placed in the inner first sealed tube.
3. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 2, characterized in that: The inner first sealed tube is a quartz glass tube, and the outer first sealed tube is a quartz glass tube; Optionally, the air pressure in the inner first sealed tube is lower than 1.0 Pa; and the air pressure in the gap between the outer first sealed tube and the inner first sealed tube is lower than 1.0 Pa.
4. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: In S2, the heating rate is 0.5 to 10 K / min, and the cooling rate is 1 to 10 K / min; Optionally, in S2, swing melting is performed during the insulation process between heating and cooling, and the swing rate is 10 to 200 times / min; Optionally, in S2, cold water quenching or natural cooling is performed after the cooling and heat preservation process is completed.
5. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: In S3, the crushing method is to crush the alloy ingot into particles with a particle size of 0.5 to 8 mm.
6. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: The second container comprises an outer second sealed tube and an inner second sealed tube disposed therein, and particles of the alloy ingot are disposed in the inner second sealed tube.
7. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 6, characterized in that: The inner second sealed tube is a quartz glass tube with a pointed bottom, and the outer second sealed tube is a quartz glass tube; Optionally, the air pressure in the inner second sealed tube is lower than 1.0 Pa; and the air pressure in the gap between the outer second sealed tube and the inner second sealed tube is lower than 1.0 Pa.
8. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: In S4, the heating rate is 0.5 to 5 K / min; Optionally, the first cooling rate is 0.01-0.05 K / min, the second cooling rate is 0.01-0.05 K / min, and the third cooling rate is 0.1-1.0 K / min.
9. The method for preparing a cubic tin selenide-based thermoelectric crystal according to claim 1, characterized in that: In S4, the second container is kept in a vertical position, and the equipment is a high temperature annealing furnace or a suspension zone melting furnace.
10. The cubic tin selenide-based thermoelectric crystal prepared by the method for preparing a cubic tin selenide-based thermoelectric crystal according to any one of claims 1 to 9, characterized in that: It is a cubic tin selenide-based single crystal with the chemical formula Sn 1-2X (AgSb) X Se, 0.1≤X≤0.3.
Citation Information
Patent Citations
Tin selenide-based thermoelectric material, preparation method and application thereof
CN111710775A
Heterogeneous doped tin selenide thermoelectric material and synthesis method thereof
CN115498093A
Preparation method of tin selenide single crystal thin film and thermoelectric device
CN117089918A
Method for regulating and controlling silver-bismuth-selenium room-temperature crystal structure based on isoelectron alloying
CN117529207A
Cubic-phase germanium selenide-based thermoelectric material and preparation method thereof
CN118714910A
Cited By
Ternary layered selenide Ge3Sb4Se7 semiconductor material and preparation method thereof
CN120736476A
A ternary layered selenide Ge3Sb4Se7 semiconductor material and its preparation method
CN120736476B